"Language Identity and Bilingualism: Nurturing Individual and Social Personalities" ("Conference on Universal Science Research 2023", 2023)
The article deals with the intricate relationship between language and identity, exploring how language shapes the formation of individual and social identities. The article begins by defining identity and recognizing language as a fundamental construct in this process. It highlights the significance of language in shaping personal and collective identities and introduces the concept of language identity as a vital aspect of self-perception.Delving further into the impact of bilingualism on language identity, the article explores how bilingual individuals navigate between linguistic systems, influencing their sense of self and belonging. It investigates the interplay between language, identity, and cultural differences, emphasizing the dynamic representation of cultural identities through language. Additionally, the article underscores the importance of cultural identity in the acquisition of foreign languages, highlighting how embracing cultural diversity can enhance language learning experiences. The article also advocates for nurturing positive language identities in bilingual contexts, recognizing the role of language in shaping individual and social personalities. Embracing language diversity and cultural richness fosters a deeper appreciation of identity, promoting inclusivity and understanding in our globalized world.